2001
DOI: 10.1021/jo001062a
|View full text |Cite
|
Sign up to set email alerts
|

Lifting of the Degeneracy in Semibullvalenes by Remote and Direct Substituents:  A Quantitative Study Using Variable-Temperature Carbon-13 NMR Spectroscopy

Abstract: A series of six 1,5-(ethylmethyl)semibullvalenes (1a <==> 1a', 2 <==> 2', 3 <==>3') and two 4(2)-substituted semibullvalenes (4 <==> 4'), each undergoing Cope equilibria between nondegenerate valence tautomers, was investigated by carbon-13 NMR spectroscopy at a range of temperatures in several different solvents. Gompper's treatment of substituent perturbation was extended, specifically accounting for the effects of the substituents on chemical shifts, to allow the determination of the thermodynamic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…[18] The solution-phase activation barrier for the Cope rearrangement in 12 is thus one of the lowest for any semibullvalene prepared to date. [16][17][18] Our semiempirical, ab initio, and DFT calculations (all of proven reliability) indicate a homoaromatic ground state for 12, while our extensive experimental investigations show that 12 is an equilibrating Cope system in the condensed phase. At all correlated levels of theory, except for B3PW91/6-31G*, the only stationary point found is the delocalized 12 c indicating that 12 resides on a single-minimum potential energy surface (PES) with a homoaromatic ground state.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…[18] The solution-phase activation barrier for the Cope rearrangement in 12 is thus one of the lowest for any semibullvalene prepared to date. [16][17][18] Our semiempirical, ab initio, and DFT calculations (all of proven reliability) indicate a homoaromatic ground state for 12, while our extensive experimental investigations show that 12 is an equilibrating Cope system in the condensed phase. At all correlated levels of theory, except for B3PW91/6-31G*, the only stationary point found is the delocalized 12 c indicating that 12 resides on a single-minimum potential energy surface (PES) with a homoaromatic ground state.…”
Section: Introductionmentioning
confidence: 92%
“…A detailed analysis of anhydride 12 and its unsymmetrical analogue 15, by variable-temperature (VT) solution and solid state NMR including modified Saunders isotopic perturbation, VT X-ray structure (293-15 K) and electron density (15 K), and VT UV/Vis and solvatochromism studies, showed that this species is not homoaromatic in the solid or solution states. [16][17][18] From the results of VT UV/Vis studies, we crudely estimated the free enthalpy difference between the localized (12 a,b) and delocalized (12 c) forms of 12 to be approximately 1.2 kcal mol À1 in a butyronitrile solution. [18] The solution-phase activation barrier for the Cope rearrangement in 12 is thus one of the lowest for any semibullvalene prepared to date.…”
Section: Introductionmentioning
confidence: 99%
“…We prepared the 1,5-(ethylmethyl) dianhydride 28 and examined its 13 C NMR spectra at a range of temperatures. [43] The 13 C spectra were obtained at 151 MHz and very precisely determined temperatures down to as low as 104 K. Again we were unable to freeze out the Cope equilibrium 28a Ǟ ǟ 28b ( 13 C NMR spetroscopy at 151 MHz down to 185 K). [35] We were unable to freeze out the Cope rearrangement of 22 or 28 in solution and, from 13 C NMR spectra at 125 MHz, we estimated the upper limit for the activation barrier of the Cope rearrangement 22a Ǟ ǟ 22b to be 3.3 kcal/mol.…”
Section: Selected Experimental Probes For Homoaromaticitymentioning
confidence: 94%
“…[43] We assumed a similar preference for the ethyl group to be on the cyclopropane ring in 28 and 32. Consequently, it was not possible to identify directly the low-energy tautomer.…”
Section: 5-dimethyl-2468-semibullvalenetetracarboxylic Acid Diimidementioning
confidence: 99%
“…62 Heubes, Quast and co-workers describe a 13 C NMR study of substituent effects on the equilibria of nearly degenerate semibullvalenes (Scheme 5). 63 This type of system may be useful in distinguishing single-versus double-well potential energy surfaces, or in transition-state spectroscopy. A series of molecules similar to 10 were studied, but only with 10 was the slow exchange limit reached.…”
Section: Cope Rearrangementsmentioning
confidence: 99%